Taking stock and effecting change: curriculum evaluation through a review of course syllabi. Issue 6 (18th August 2018) - Goodwin, Adam; Chittle, Laura; Dixon, Jess C.; Andrews, David M.
Abstract: A multi-disciplinary academic unit at a Canadian university completed an evaluation of course syllabi used in its undergraduate programmes over the previous five years. This paper examines the reasons for the evaluation, the processes employed to collect and analyse the data, and how the results will be incorporated into the next steps of the overall curricula reform planned within the unit. The evaluation focused on the unit's adherence to departmental and university policies, course reading materials, experiential learning opportunities, forms of assessments (e.g. types and weighting of assignments), learning outcomes and instructor-specific policies (e.g. group work expectations, late assignments). While a summary of the results of the evaluation are provided herein, these are meant to highlight the administrative and curricular benefits and uses of the data, rather than an analysis and discussion of the results themselves.